HAMBATAN BONGKAR MUATSCRAP WAKTU SANDAR KAPAL DI DERMAGA TERMINAL MULTIPURPOSE TANJUNG PRIOK - Capt Berlian Badarusman; Gartika Eryana (Institut Transportasi dan Logistik Trisakti, 2016)
PT. Multi Terminal Indonesia is a terminal operator specialized in loading and unloading goods in containers and bulk cargo. The purpose of this research is to find out the factors created the obtacles when loading and unloading scrap, the real problems and effective solutions need to be taken by the company. The research is using fishbone diagram. Using the questionnaire response, the researchers get the factors which are: 1. Materials (the on time performance of trucking part), 2. Machines (loading and unloading complete facilities and equipment), 3. Facilities (Back up area), 4. Machines (the number of loading and unloading scrap), 5. Materials (the number of trucking for each shift). The effective solutions are the company should provide some armadas to be used when in need and ask the owner to prepare everytime in need.